OKTAY RİFAT'IN ŞİİRLERİNİN VE ROMANLARININ İNCELENMESİ - ÖZCAN, TARIK (Fırat Üniveristesi, 1999)
Bu çalışmada Oktay Rıfat'ın şiirleri ve romanları incelenmiş ve sanat anlayışına ışık tutulmuştur. Gerek şair ve yazar hakkında yazılan kaynaklardan gerekse şair-yazarın kendi yazdığı kaynaklardan elde edilen bilgilerle 20. yüzyıl şair-yazarı Oktay Rıfat'ın hayatı. kişiliği, sanat ve edebiyat anlayışı tespit edilmiştir. Aynı zamanda Oktay Rıfat'ın şiirleri ve romanları incelenerek analiz edilmiştir. Bu çalışma ile kültür mirasımızın önemli bir şair-yazarı hakkında geniş bir bilgiye sahip olunmuştur. Anahtar Kelimeler: Oktay Rifat, Yirminci Asır, Garip

In this study, poetries and novels of Oktay Rifat of is examined and art understanding of his is brought to light. Through information, acquired either by the present sources related with the poetr- writer or by the works writer/poetry; the life, personality, artistic and literaty aspect and influence of the twenty century poetry-writer Oktay Rifat have been determined. İn the examination part of the thesis, Oktay Rifat's poetries and novels is analysed. With the work; an importan poetry-writer of on cultural heritage has been evaluated. Key Words: Oktay Rifat, Twenty Century, Strange (Destitute)
The Examinant of Oktay Rifat's poetries and novels
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature